Arabia: The Gulf and the West - J.B. Kelly (U.S.A Basic Books, 1980)
This meticulously researched book provides a timely and absolutely indispensable guide to the nations of the Persian Gulf on which the West's security and oil supplies critically depend- their political regimes and policies, their economies and the mind-sets of their leaders. But it does more than that. Dr. Kelly, one of the world's leading authorities on the modern history of Arabia and the Gulf, for the first time tells the full story of how the West's supine policies deliberately pulled us out of the region and thus led inevitably to the dangerous power vacuum that now exists in the world's most important strategic area. The author also shows that one cannot fully understand the dangerous situation in which the West now stands with regard to its oil supplies without understanding the nature of the regimes in power in the Arabian peninsula.